Peroxidase mimetic activity of fluorescent NS-carbon quantum dots and their application in colorimetric detection of H2O2 and glutathione in human blood serum - Singh V.K.; Yadav P.K.; Chandra S.; Bano D.; Talat M.; Hasan S.H. (My University, 2025)
Interest is growing in the development of artificial enzymes to overcome the drawbacks of natural enzymes. Herein, we have synthesized nitrogen-sulphur dual-doped carbon quantum dots (NS-CQDs) via a one-step hydrothermal method; the NS-CQDs possess excellent optical properties and a high fluorescent quantum yield (46%). Significantly, the NS-CQDs exhibited peroxidase mimetic enzyme activity without support from metals or polymeric materials and efficiently catalyzed the oxidation of peroxidase substrate 3,3,5,5-tetramethylbenzidine (TMB) in the presence of H2O2 to produce a blue solution with an absorption maximum at 652 nm. Mechanistic studies suggest that the small size and high electron density of NS-CQDs play vital roles and accelerate the reduction of H2O2 to generate OH radical, which facilitates the oxidation of TMB. The catalytic activity is based on Michaelis-Menten kinetic behavior, and steady state kinetic analysis suggests that the NS-CQDs exhibit a higher affinity for H2O2 than TMB, similar to the natural enzyme horseradish peroxidase (HRP). Moreover, the catalytic pathway follows a ping-pong mechanism. Therefore, these findings offer a worthy platform for colorimetric detection of H2O2 in a linear range of 0.02 mM to 0.1 mM with a limit of detection of 0.004 mM. Interestingly, the blue colour of oxidized TMB showed excellent selectivity over non-thiolate biological molecules, especially amino acids, and glutathione can be detected up to 0.07 μM via colorimetric and fluorimetric assays. Additionally, this system showed excellent recovery (96.0-108.3%) of GSH from human blood serum. Thus, the proposed sensing system is simple, convenient, and straightforward and can be potentially applied for real time monitoring of H2O2 and glutathione in biological samples. © 2018 The Royal Society of Chemistry.